Circadian variations in electric current responses at ryodoraku points across the waking stage: A prospective observational study. Issue 9 (March 2019) - Bae, Jang-Han; Ku, Boncho; Bae, Se-Eun; Kim, Jaeuk U.
Abstract : Abstract: Human body undergoes the 24-hour daily rhythm in response primarily to light and darkness. The circadian rhythms of biomarkers reflect bodily conditions including the prognosis of some pathologies. As a sensitive index of sympathetic nervous response (SNR), electrodermal activity (EDA) is a recent research topic in healthcare industry as a noninvasive and easy-access biosignal. The EDA response at Ryodoraku points (RPs) is of potential clinical usage in relation to SNR and meridian theory, but still remains in its primitive development stage. In this study, the 24-hour variations of EDA for 14 hospitalized participants were monitored over 3 days using a Ryodoraku device, and a circadian model of EDA was constructed using a cosinor analysis based on the linear mixed effect model. As a result, EDA at every RP showed a circadian cycle with its value the lowest in the morning and increased gradually until the late afternoon, and monotonically decreased again until the next morning. Circadian variations were observed in EDAs of all 12 RPs. However, Ryodoraku-specific features were not detected. Midline estimating statistic of rhythm (MESOR) values in men and young group were higher than in women and old group, and cosinor analysis showed significant circadian rhythms, especially for men and young groups. Especially, circadian variation in EDA in the young group went above 35% of the MESOR value. It implies that the circadian rhythm should be considered for the Ryodoraku analysis to examine bodily conditions or the prognosis of some pathologies. Abstract : Supplemental Digital Content is available in the text